Associations between grass pollen exposures in utero and in early life with food allergy in 12-month-old infants. Issue 4 (3rd April 2022) - Susanto, Nugroho Harry; Lowe, Adrian J; Salim, Agus; Koplin, Jennifer J.; Tang, Mimi L. K.; Suaini, Noor H. A.; Ponsonby, Anne-Louise; Allen, Katrina J.; Dharmage, Shyamali C.; Erbas, Bircan
ABSTRACT: Birth during pollen seasons may influence food allergy risk but no study has assessed pollen exposure. Using the HealthNuts population-based cohort of 5276 infants, we assessed grass pollen exposures, in utero and up to the first 6 months of life, on hen's egg, sesame and peanut allergy outcomes at 12 months. Cumulative pollen exposure in the first 7 days of life increased risk of peanut sensitization aMOR (adjusted multinomial odds ratio) = 1.21 (95% CI: 1.01–1.44). Exposure between first 4–6 months of life increased risk of hen's egg aMOR = 1.02 (95% CI: 1.004–1.04) and sensitization to all foods aMOR = 1.02 (95% CI: 1.003–1.04). Grass pollen exposure was associated with food challenge diagnosed food allergy, but only among infants with a maternal history of food allergy. Exposure to grass pollen in the intrauterine period and infancy may be important but more studies are needed to replicate these findings.